Dunia tanpa tirai : kumpulan esei sosiopolitik - S. M. Zakir (Syed Mohd. Zakir), 1969- ([Kajang, Selangor D.E. i.e. Darul Ehsan] : Pustaka Nusa, 2009)
Contemporary issues on sociopolitical conditions in Malaysia; collected articles.
In Malay.
Keywords: Malaysia -- Politics and government -- 21st century; Malaysia -- Social conditions -- 21st century